Sex differences in the association between muscle mass or strength and nutrition status in chronic hemodialysis patients - Yosuke Tayama; Tomonari Ogawa; Yoshimi Konishi; Kanae Takahashi; Koichiro Fujii; Ayumi Shintani; Hajime Hasegawa (Renal Replacement Therapy)
Abstract Background In the field of dialysis, studies focusing on sex differences have become increasingly common. However, there are few reports examining whether differences exist between sexes in the association between muscle mass, muscle strength, and nutritional status. This study aimed to investigate the association between muscle mass, muscle strength, and nutrition in dialysis patients, with a specific focus on sex differences. Methods This single-center, retrospective, cross-sectional, and observational study was conducted from October 2018 to February 2019. We enrolled 89 patients undergoing regular hemodialysis at a single dialysis center (Imus Fujimi General Hospital, Saitama, Japan). The relationship between skeletal muscle index (SMI; measured by bioelectrical impedance analysis), handgrip strength, and nutritional status (as assessed by the Geriatric Nutritional Risk Index, GNRI), along with other biochemical parameters, was analyzed separately for men and women. Results A positive association was observed between SMI and GNRI (P-for-GNRI < 0.001). In women, the relationship was nonlinear, presenting a U-shaped pattern, although this was not statistically significant (P-for-nonlinear = 0.085). No association was found between SMI and normalized protein catabolic rate (nPCR; P-for-nPCR = 0.628). SMI and C-reactive protein (CRP) showed a significant nonlinear U-shaped relationship (P-for-nonlinear = 0.001). Although a negative association could not be confirmed, a significant association was observed (P-for-CRP = 0.001). In women, SMI was maintained even at higher CRP levels. GNRI and CRP also exhibited a significant nonlinear U-shaped relationship (P-for-nonlinear = 0.012), with a notable association despite the absence of a clear negative correlation (P-for-CRP = 0.002). In women, GNRI was preserved even when CRP levels were elevated. Conclusions An association was found between muscle mass, muscle strength, and nutrition. Women exhibited a nonlinear relationship, distinct from men, suggesting that women may require more robust nutritional management compared with men. Furthermore, the direct association between inflammation and nutrition appeared more prominent in men, whereas the association in women was less distinct. However, the influence of the small sample size of female participants in this study cannot be ruled out, and larger-scale clinical studies are needed.